Infol Traitements : mensuel d'information sur les traitements. (Paris : Action Traitements.)
Fonds Suzan Daniel (FSD)
Periodiciteit: maandelijks
Redactie: 190 boulevard de Charoinne, 75020 Paris
Frans
Periodiek